The articulation of massmedia and social media: exploring civic movements in Portugal - Dias, Patrícia (2014)
Each time a new communication medium is introduced and reaches relative generalization, it creates new balances and articulations among the existing media, thus reconfiguring the whole mediatic and communicational landscape (Bolter and Grusin, 2000; Jenkins, 2006). In contemporary society, two types of media with totally different characteristics and operating logics coexist, articulate and converge among themselves – massmedia and social media – resulting in a new way of communicating, describes by Manuel Castells (2009) as mass-self communication. Within public relations, several authors recognize a transition from asymmetric communication theories and models, in which organizations publicize information a strongly control their messages, to more symmetric conversation and dialogic models that are emerging as a consequence of PR professionals using social media as communication channels and tools (Kunsch, 2003; Solis and Breakenridge, 2009; Scott, 2010; Macnamara and Zerfass, 2012). Although most of these authors highlight the loss of control over their messages that organizations are undergoing, others explore the emergence of new power balances that are not necessarily symmetric or equalitarian (Edwards and Hodges, 2001; Coombs and Holladay, 2012; Dutta, Ban and Pal, 2012). This paper explores civic movements as an example of the new articulations among massmedia and social media that emerging, as well as new power balances between the public, media and politic agendas (McCombs and Shaw, 1972). Using qualitative methods, this paper empirically explores the recent civic movements against austerity in Portugal, that culminated with the demonstrations “Geração à Rasca” [‘Precarious’ Generation] (12th March 2011) and “Que se lixe a Troika!: Queremos as nossas vidas” [Screw Troika! We want our lives back] (15th September 2012), discussing the articulation of massmedia and social media that was done both by citizens and communication professionals (PRs and journalists, as well the role played by each of these types of media in publicizing, mobilizing and in the social impact of these movements.